The Effect of Entrepreneurial Spirit, Creativity, and Business Capital on Business Sustainability with Innovative Excellence as an Intervening Variable - Zikri, Inanda; Suhardi, Suhardi; Radiansyah, Adrian (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the influence of creativity, venture capital, and entrepreneurial spirit on business sustainability, with innovation excellence as a mediating variable in the Micro, Small, and Medium Enterprises (MSMEs) sector. The background of this study lies in the crucial role of innovation in strengthening the competitiveness and sustainability of MSMEs in the midst of a constantly changing business environment. The method used is a quantitative approach using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). Data were collected through closed questionnaires distributed to 150 active MSME actors in Pangkalpinang. The results of the analysis show that creativity and venture capital significantly and indirectly affect business sustainability through innovation excellence. Innovation excellence is proven to be a significant mediating variable, strengthening the relationship between internal business factors and sustainability. In contrast, entrepreneurial spirit does not show a significant influence, either directly or indirectly, through innovation. These findings emphasize that business strategies that focus on increasing innovation and creativity, supported by adequate access to capital, are more effective in creating sustainable companies.